2014
DOI: 10.1093/carcin/bgu007
|View full text |Cite
|
Sign up to set email alerts
|

β-1,4-Galactosyltransferase III suppresses β1 integrin-mediated invasive phenotypes and negatively correlates with metastasis in colorectal cancer

Abstract: Metastasis often occurs in colorectal cancer (CRC) patients and is the main difficulty in cancer treatment. The upregulation of poly-N-acetyllactosamine-related glycosylation is found in CRC patients and is associated with progression and metastasis in cancer. β-1,4-Galactosyltransferase III (B4GALT3) is an enzyme responsible for poly-N-acetyllactosamine synthesis, and therefore, we investigated its expression in CRC patients. We found that B4GALT3 negatively correlated with poorly differentiated histology (P … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 36 publications
2
26
1
Order By: Relevance
“…[17] Increased expression of some glycosyl moieties promotes invasion and metastasis, leading to shorter patient survival rates, whereas expression of other glycosyl epitopes suppresses tumor progression, resulting in higher survival rates. [26] Inflammation and immune function are united in the pathogenesis of cancers[27, 28] and underlie the mechanistic importance of protein post-translational glycosylation in the pathogenesis of CRC. [29]…”
Section: Resultsmentioning
confidence: 99%
“…[17] Increased expression of some glycosyl moieties promotes invasion and metastasis, leading to shorter patient survival rates, whereas expression of other glycosyl epitopes suppresses tumor progression, resulting in higher survival rates. [26] Inflammation and immune function are united in the pathogenesis of cancers[27, 28] and underlie the mechanistic importance of protein post-translational glycosylation in the pathogenesis of CRC. [29]…”
Section: Resultsmentioning
confidence: 99%
“…Increased β4GalT1 expression and activity is significantly correlated with differentiation and mobilization of granulocytes and with the metastatic potential of specific cancer cells 37,[60][61][62][63][64] . Modifications of LacNAc by sialic acid and Gal decorations on α4β1 or α5β1 negatively affect cell-cell and cell-matrix interactions, thereby increasing cancer cell mobility in colon adenocarcinoma, ovarian cancer, and hepatocellular carcinoma 37,[64][65][66][67][68][69] . Control MKs express two β1 integrin glycoforms at 130 and 110 kDa, while platelets express the 130 kDa β1 glycoform primarily.…”
Section: Parametermentioning
confidence: 99%
“…[24] Recently, it has been reported that B4GALT3 protein plays an important role in invasion, proliferation, and metastasis in extravillous trophoblast, colorectal cancer, and neuroblastoma. [252627] The mutation of B4GALT3 gene was first identified in a POAG pedigree. POAG is a complex neurodegenerative disease which results in the stress in retinal ganglion cells and optic nerve axons.…”
Section: Discussionmentioning
confidence: 99%